ANALYSIS OF CAR BODY AERODYNAMICS WITH VARIATION OF SPEED USING CFD SOFTWARE - Gde Didit Citra Budgeta, Bagus (SATUKATA: Jurnal Sains, Teknik, dan Studi Kemasyarakatan, 2022)
The car is one of the most common vehicles used to meet transportation needs around the world. In the development of technology in cars, one of the influencing factors is the body design of the car. When designing a car, there are several aspects that need to be considered, one of which is the drag coefficient. In this study, a car body shape will be designed for further simulation and analysis with the help of the ansys 2020 software. Comutational fluid dynamics can analyze or predict the fluid flow in the car body. The formation process includes Preprocessing, Solving, and Postprocessing. The analysis was carried out on three-dimensional (3D), steady, turbulent flow. The variable is used to analyze the speed of the wind that will be passed by the car body, with a range of 15m/s, 30m/s, and 45m/s.